Analysis of The Debtor's Endurance using Cox Regression Semiparametric Method - Handayani*, Vitri Aprilla; Reza, Widya; Anggraeni, Andini Setyo; Rusmadi, Garry (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The aim of this research was conducted to determine the factors that influence the resilience of car loan debtors in an area. The research method used is semiparametric Cox regression on secondary data, WAREHOUSE consisting of the customer profile (demography) and historical payment consisting of 25 observed variables. The Cox regression model used in this study is a proportional hazard Cox regression model. Based on the description of the data, it shows that there is a risk of defaulting debtors who have been past due compared to never past due. Cox proportional hazard regression model with the semiparametric method can be used to identify factors that affect debtor resilience. Of the 25 variables observed, there is one variable, namely the X16 (Age) variable which does not significantly affect the debtor's endurance. Keywords: Debtor Resistance; Historical Payment; Semiparametric; Cox Regression; Proportional Hazard Penelitian ini bertujuan untuk mengetahui faktor yang berpengaruh terhadap daya tahan debitur kredit mobil di suatu wilayah. Metode penelitian yang digunakan pada penelitian ini adalah semiparametric regresi cox pada data sekunder, warehouse yang terdiri profil (demographi) customer dan historycal payment terdiri atas 25 varibel yang diamati. Model regresi Cox yang digunakan pada penelitian ini adalah model regresi Cox hazard proporsional. Berdasarkan deskripsi data menunjukkan adanya risiko debitur gagal bayar yang Pernah Past Due dibandingkan Never Past Due. Model regresi cox proportional hazard dengan metode semiparametrik dapat digunakan untuk mengedentifikasi faktor-faktor yang mempengaruhi daya tahan debitur. Dari 25 variable yang diamati ada 1 (satu) variable yaitu peubah X16 (Age) yang tidak signifikan berpengaruh terhadap daya tahan debitur. Kata Kunci: Daya Tahan Debitur; Riwayat Pembayaran; Semiparametrik; Regresi Cox; Proporsi Hazard